Thrash Deplorer System Using IoT Through Web Application - Kishore, K. Lalith; Jaswanth, P; Abhyuday, S.B.T; Jayasairam, Y (International Journal of Computer Sciences and Engineering, 2025)
Today’s generation has a great need of cleanliness and health plays an important role in their life so that our surroundings must be clean. This can be achieved through this paper and in this paper it mainly deals about the overfilling of garbage bins in our society. The bin status can be observed by the municipal officer in his office and knowing continuous monitoring of the bin status through the web application using IoT. The filling of the bins can be determined by two methods one is by weight and the other is the level. This can reduce the manual monitoring and continuous keen observation on the bin can be prevented .In this paper mainly deals about the sensors like weight and ultrasonic sensors, a node Microcontroller Unit (MCU) and an IoT platform which acts as an interface with the hardware part and the software part in which the application is present. The hardware part can be connected on the Arduino in which all the sensors can be interfaced along with NodeMicroControllerUnit (MCU).